RECONSTRUCTION OF ISLAMIC EDUCATION CURRICULUM MANAGEMENT BASED ON DEEP LEARNING IN THE ERA OF DIGITAL TRANSFORMATION - Masruroh, Siti; Rahmatiani, Lusiana; Hananto, Agustia; Utomo, Ainur Alam Budi; Ali, Agus (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The reconstruction of the Islamic Education (PAI) curriculum is essential in responding to the changes brought by the digital era. Purpose: This article proposes a deep learning–based curriculum management model for Islamic education as a form of digital transformation within Islamic educational institutions. The approach emphasizes the development of deep understanding, spiritual reflection, and the integration of Islamic values into all aspects of the curriculum. Method: The research employs a conceptual-theoretical (library research) approach with a comparative analysis of literature on curriculum management, deep learning theory, and best practices in contemporary Islamic education. Result: The findings reveal key components of deep learning–based curriculum management, including adaptive curriculum design, data-driven teacher training, longitudinal evaluation, and managerial-technological synergy. Conclusion: Practical recommendations are directed toward transforming curriculum policies in madrasahs and Islamic schools.